(Mis)versioning as a quality assurance compromise in the development of numeracy curriculum in African languages. Issue 1 (2nd January 2023) - Lepota, Biki
Abstract: Along with literacy, numeracy is considered a critical skill that impacts on the success or failure of learners in the formative stages of the schooling system. In the context of the Language in Education Policy, which accords every learner in every public school the right to use the language of their choice in the process of being educated, the numeracy learning area should be taught and learnt in Sepedi. To operationalise this policy provision, curriculum policymakers generally subject learning materials available in English to a translation process and make them available in the various official African languages. This paper discusses the challenges encountered in translating numerical word expressions from English into Sepedi and offers, from a linguistic point of view, solutions to deal with the challenges encountered. Data were collected from existing Sepedi literature, and an analysis was conducted of how numerical word expressions are used and treated relative to how they were translated. To validate the literature's authenticity in the use of the concepts under discussion, a survey was conducted amongst mature and home-language users of Sepedi. The findings show that there are contradictions in how plural forms of numerical word expressions are used by Sepedi language professionals, as is the case in other literature. This creates a problem for the teaching and assessment of these concepts in the foundation phase of the schooling system. Based on the available evidence, the paper makes an argument against the use of bo - when pluralising cardinal numbers in the context of numeracy. The paper concludes with a call for Umalusi to implement systems to quality-assure learning materials translated from English into African languages.